DESAIN DIDAKTIS KONSEP TEOREMA SISA PADA PEMBELAJARAN MATEMATIKA SEKOLAH MENENGAH ATAS (SMA) - Artanti, Dhias Mei (2013)
Learning math by using materials that do not conform to the characteristics of students will result in learning mathematics is not intact, the meaning and the context will be poor, so that would lead to the emergence of barriers to learning (learning obstacle). Assignment of teachers to overcome it by making the didactic design comes with a variety of student responses during the anticipation of learning. Initial didactic design applied then get tested for improvement for the next didactic design.The measures were formally formulated into an activity of research called Didactical Design Research (DDR). This study focused on the concept of teorema sisa. The subjects of the research were students of class XII IPA of 3rd cluster for testing learning obstacle, while the students of class XI IPA of 2nd cluster to test didactic design. The approach used in this study was qualitative with descriptive analysis methodology . Results of this study was the discovery of the five types of learning obstacle (1) learning obstacle-related to concept image (2) learning obstacle related to modeling (3) learning obstacle associated with fluency procedure (4) learning obstacle associated with a connection (5) learning obstacle associated with variety information. Furthermore the author prepared design didactic by concerning to the learning obstacle that has been identified and the response or students' answer, then to be adjusted by the relevant learning theory. At the time of initial didactic design implementations, most of the responses of students in accordance with the previously predicted. from the analysis after the implementation of early learning didactic design showed that student understanding after getting learning concept of teorema sisa with initial didactic design, were better than the students who have earned the concept teorema sisa with learning materials based on textual understanding. So the initial didactic design aimed as an alternative to reduce the appearance of learning obstacle to the concept of Teorema Sisa and considered quite appropriate to improve learning. Keywords: Learning Obstacle, Design didactic, Didactical Design Research (DDR), Teorema Sisa. Pembelajaran matematika dengan menggunakan bahan ajar yang tidak sesuai dengan karakteristik siswa akan menghasilkan proses belajar matematika yang tidak utuh, miskin makna dan konteks, sehingga akan menyebabkan munculnya hambatan belajar (learning obstacle). Tugas guru untuk menanggulangi hal tersebut yakni melalui pembuatan desain didaktis yang dilengkapi dengan beragam antisipasi respon siswa selama pembelajaran. Desain didaktis awal diujicobakan untuk kemudian mendapatkan perbaikan demi penyempurnaan desain didaktis selanjutnya. Langkah-langkah tersebut dirumuskan secara formal kedalam suatu aktivitas penelitian yang disebut dengan Didactical Design Research (DDR). Penelitian ini difokuskan pada konsep teorema sisa. Subjek penelitian meliputi siswa kelas XII IPA dari 3 kluster dan mahasiswa untuk uji learning obstacle, sedangkan siswa kelas XI IPA dari kluster 2 untuk uji desain didaktis. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dengan metode deskriptif analisis. Hasil dari penelitian ini adalah ditemukannya lima tipe learning obstacle yakni (1) learning obstacle terkait dengan concept image (2) learning obstacle terkait dengan modeling (3) learning obstacle terkait dengan fluency procedure (4) learning obstacle terkait dengan connection (5) learning obstacle terkait dengan variation information. Selanjutnya disusun desain didaktis dengan mempertimbangkan learning obstacle yang telah teridentifikasi dan memperhatikan respon atau jawaban siswa, serta disesuaikan pula dengan teori belajar yang relevan. Pada saat implementasi desain didaktis awal, sebagian besar respon siswa sesuai dengan yang telah diprediksikan sebelumnya. Analisis setelah implementasi pembelajaran desain didaktis awal menunjukkan bahwa pemahaman siswa setelah mendapatkan pembelajaran konsep teorema sisa dengan desain didaktis awal lebih baik daripada siswa yang telah mendapatkan pembelajaran konsep teorema sisa dengan bahan ajar yang didasarkan pada pemahaman tekstual. Sehingga desain didaktis awal yang bertujuan sebagai alternatif untuk mengurangi munculnya learning obstacle pada konsep teorema sisa dinilai cukup tepat digunakan untuk memperbaiki pembelajaran. Kata Kunci : Learning Obstacle, Desain Didaktis, Didactical Design Resesarch (DDR), Teorema Sisa.